Seja f uma função afim f(x)= ax+b determine - a sabendo que :
a) f (2)=5 e f(-1)=-4
Soluções para a tarefa
Respondido por
2
f(x)=ax+b
f(2)= a.2 + b = 5
2a + b = 5
b = 5 - 2a ←vamos usar no f(-1).
f(-1) = a.(-1) + b = -4
-a + (5 - 2a) = -4
-3a = -4 - 5
-3a = -9 .(-1)
3a = 9
a = 9/3
→a = 3←
b=5-2a
b= 5 - 2.3
b= 5 - 6
→b = -1←
f(x) = 3x -1
"determine - a"
- a = - 3
b - a = -1 - 3 = -4
a - b = 3 - (-1) = 3 + 1 = 4
f(2)= a.2 + b = 5
2a + b = 5
b = 5 - 2a ←vamos usar no f(-1).
f(-1) = a.(-1) + b = -4
-a + (5 - 2a) = -4
-3a = -4 - 5
-3a = -9 .(-1)
3a = 9
a = 9/3
→a = 3←
b=5-2a
b= 5 - 2.3
b= 5 - 6
→b = -1←
f(x) = 3x -1
"determine - a"
- a = - 3
b - a = -1 - 3 = -4
a - b = 3 - (-1) = 3 + 1 = 4
Perguntas interessantes